Quantum tempest [large type] - Cussler, Clive; Maden, Mike (Cussler, Clive. Oregon files adventures, 2025)
"There's a tempest brewing in Central America. A government crackdown on cartels leaves most of the drug lords locked up in an impregnable prison. In response, Amador Fierro, a brilliant, tech-savvy crime boss forges the seven largest cartels into an allegiance called La Liga. If they are to defeat the U.S. led offensive, they will need a powerful weapon. Thus is born Project Q: an Artificial General Intelligence computer that, when finished, will grant Fierro such overwhelming control of America. Chairman Juan Cabrillo and the crew of the Oregon are the only ones standing in his way, but they have their own problems. While two members of the team are unreachable in the Darien Gap searching for an Iranian Quds Force base, the Oregon crew have a mole in their midst. Meanwhile, other dark forces are at play, competing for the all consuming power at hand. The race to stop the launching of Project Q will come down to the wire, but it's a race neither Juan Cabrillo, nor the western world, can afford to lose" -- Provided by publisher.